Patient Satisfaction and Quality of Life Outcomes Following Dental Implant Placement - Nabarun Chakraborty; Ban A. Almudarris; Parthsarthi Gautam; Rashmi Laddha; Tapan K. Giri; Vishal D. Patel (Journal of Pharmacy and Bioallied Sciences)
Background: Dental implants have become a standard solution for the replacement of missing teeth, significantly influencing patient satisfaction and quality of life. This study aims to evaluate patient satisfaction and quality of life outcomes following dental implant placement. Materials and Methods: A total of 150 patients who received dental implants were included in this study. Patient satisfaction was assessed using a validated questionnaire covering various aspects such as esthetics, function, and comfort. Quality of life was evaluated using the Oral Health Impact Profile (OHIP-14). Data were collected at baseline (prior to implant placement) and at a 6-month follow-up. Results: Of the 150 patients, 135 (90%) completed the 6-month follow-up. The overall patient satisfaction score improved significantly from a baseline mean of 3.5 (SD = 1.2) to 8.2 (SD = 1.1) at the 6-month follow-up (P < 0.001). Similarly, the OHIP-14 score showed a significant reduction, indicating improved quality of life, from a baseline mean of 32.0 (SD = 5.3) to 14.5 (SD = 4.2) at the 6-month follow-up (P < 0.001). Subscales for pain, psychological discomfort, and social disability showed marked improvements. Conclusion: Dental implant placement leads to a significant increase in patient satisfaction and quality of life. These findings underscore the importance of dental implants as a viable option for the restoration of missing teeth and the enhancement of overall oral health and well-being.